Sleep Disturbance and Short Sleep as Risk Factors for Depression and Perceived Medical Errors in First-Year Residents - Kalmbach, David A. (Sleep, 2017)
STUDY OBJECTIVES: While short and poor quality sleep among training physicians has long been recognized as problematic, the longitudinal relationships among sleep, work hours, mood, and work performance are not well understood. Here, we prospectively characterize the risk of depression and medical errors based on preinternship sleep disturbance, internship-related sleep duration, and duty hours. METHODS: Survey data from 1215 nondepressed interns were collected at preinternship baseline, then 3 and 6 months into internship. We examined how preinternship sleep quality and internship sleep and work hours affected risk of depression at 3 months, per the Patient Health Questionnaire 9. We then examined the impact of sleep loss and work hours on depression persistence from 3 to 6 months. Finally, we compared self-reported errors among interns based on nightly sleep duration (≤6 hr vs. >6 hr), weekly work hours (<70 hr vs. ≥70 hr), and depression (non- vs. acutely vs. chronically depressed). RESULTS: Poorly sleeping trainees obtained less sleep and were at elevated risk of depression in the first months of internship. Short sleep (≤6 hr nightly) during internship mediated the relationship between sleep disturbance and depression risk, and sleep loss led to a chronic course for depression. Depression rates were highest among interns with both sleep disturbance and short sleep. Elevated medical error rates were reported by physicians sleeping ≤6 hr per night, working ≥ 70 weekly hours, and who were acutely or chronically depressed. CONCLUSIONS: Sleep disturbance and internship-enforced short sleep increase risk of depression development and chronicity and medical errors. Interventions targeting sleep problems prior to and during residency hold promise for curbing depression rates and improving patient care.